Proposed new interior design of Nescafe Coffee House at No. 1 , Jalan U-Thant, Jalan Tun Razak, 55000 Kuala Lumpur / Nur ‘Aini Mohamad Adini - Mohamad Adini, Nur ‘Aini (Faculty of Architecture, Planning and Surveying, 2010)
This broad definition excludes restaurants which are distinguished by the emphasis on food preparation and consumption. The cafe may also serve food, but eating is neither a condition for use nor has it had a fundamental effect on the planning and arrangement of the establishment. Even so, the variety of individual solutions for the programme of the cafe is vast, indeed, so large that attempts at a systematic categorization are difficult. Other than that, the present cafe mostly didnt emphasize the truly cafe are. Mostly they are not study deeply into the cafe design rather than thinking about gething profit. So, i would like to Proposed New Interior Design For Nescafe Coffee House. Why i choose Nescafe? Firstly, Nescafe is a famouse brand coffee which is been drink to whole world and the level of sales this product are veryhigh. So, i sure that, if Nescafe Coffee House been realize in Malaysia, it would attract people to come dine into it while comercialize Malaysia brad to worldwide. Hopefully with my idea and my design of this coffee house will give a liltle bit idea to those who decide or thinking to open this Nescafe Coffee House.